Epistemic Curiosity as a Predictor of Psychological Well-Being: A Correlational Analysis - Ibad, M. Choirul; Mora, Linda; Dimala, Cempaka Putrie (Universitas Islam Negeri Raden Intan Lampung, 2025)
The advancement of knowledge and the abundance of information can trigger confusion, information fatigue, and uncertainty that have an impact on an individual's psychological well-being. This study has three hypotheses, with one main hypothesis being to test the relationship between epistemic curiosity and psychological well-being. There are two remaining hypotheses testing the dimensions of epistemic curiosity on psychological well-being. This study uses a quantitative correlational approach with two instruments: epistemic curiosity and psychological well-being. The participants obtained were 376 students who were taken using convenience sampling and snowball sampling techniques. The results of this study did not find a significant relationship between epistemic curiosity and psychological well-being. However, Deprivation-Type Curiosity as a dimension of psychological well-being was not proven to be substantial for psychological well-being. In other words, a high level of curiosity can have positive or negative impacts, depending on the various factors that influence it. Therefore, it is important to investigate mediating or moderating variables in subsequent studies.Keywords: epistemic curiosity, psychological well-being, correlational study, mental health